Direct comparison of gamma, electron beam and X-ray irradiation doses on characteristics of low-density polyethylene, polypropylene homopolymer, polyolefin elastomer and chlorobutyl rubber medical device polymers. (September 2021) - Fifield, Leonard S.; Pharr, Matt; Staack, David; Pillai, Suresh D.; Nichols, Larry; McCoy, James; Faucette, Tony; Bisel, Tucker T.; Huang, Min; Hasan, Md Kamrul; Perkins, Lucas; Cooley, Scott K.; et al.
Abstract: There is a growing need for increased efficiency in the sterilization of single use medical devices and other products that contain polymer components. Gamma radiation is widely used for devices suited for radiation sterilization; however, safety, throughput and cobalt-60 source availability are challenging the prospect of relying on gamma radiation to meet the anticipated needs of the industry. Use of electron beam (e-beam) and X-rays as alternatives to gamma for radiation sterilization have been hampered in part by a concern that these modalities may adversely affect polymer integrity and performance relative to the gamma method, for which the industry has had much more experience. To address this concern, the effects of sterilization-relevant doses of e-beam, X-ray and gamma radiation were directly compared using common medical device polymers found in two prototypical commercial devices currently sterilized using cobalt-60 gamma irradiation. The Becton, Dickinson and Company (BD) Vacutainer™ Plus tube contains low-density polyethylene and chlorobutyl rubber components, while the BD Vacutainer™ Push Button Blood Collection Set contains polypropylene homopolymer and polyolefin elastomer components. Injection-molded samples prepared from the polymers used in these products were exposed to target doses of 15, 35, 50 and 80 kGy using gamma, e-beam and X-ray radiation. Changes in coloration, tensile properties and hardness were measured for each condition, and the effects of e-beam and X-ray irradiation compared with the effects of gamma irradiation on these properties. Both e-beam and X-ray appear as viable alternatives to gamma irradiation for sterilization of the polymers tested. Highlights: Electron beam and X-rays are alternatives to gamma for radiation sterilization. Gamma, electron beam, and X-ray effects on polymers were directly compared. Injection-molded samples were exposed to 15, 35, 50 and 80 kGy dose levels. Color, tensile, and hardness properties were measured before and after irradiation. Results support both e-beam and X-ray as viable irradiation sterilization options.